Banking structure and industrial growth: Evidence from China - Lin, Justin Y.; Sun, Xifang; Wu, Harry X. (Journal of Banking & Finance, 2015)
The debate on the puzzling relationship between financial development and economic growth in China has remained inconclusive because the effects of banking ownership structure and size structure are highly intertwined in the existing studies. This paper addresses this problem by specifying an empirical model to disentangle the two structural effects. The analysis uses a data set that includes the banking sector and 28 manufacturing industries across 30 Chinese provinces over the period 1999–2007. In order to identify the channel through which banking structure affects industrial growth, two interactive variables are constructed to capture the interaction of the prevailing banking structure with labor intensity and the share of non-state-owned enterprises in each industry, respectively. The regression results are robust and make the case for the ongoing banking reforms to reduce state ownership and promote small banking institutions.